Promoter Methylation of the MGRN1 Gene Predicts Prognosis and Response to Chemotherapy of High-Grade Serous Ovarian Cancer Patients - Li, Xiao-fei; Sun, Hai-yan; Hua, Tian; Zhang, Hai-bo; Tian, Yun-jie; Li, Yan; Kang, Shan (Frontiers in Oncology, 2021)
Aberrant DNA methylation is considered to play a critical role in the chemoresistance of epithelial ovarian cancer (EOC). In this study, we explored the relationship between hypermethylation of the Mahogunin Ring Finger 1 (MGRN1) gene promoter and primary chemoresistance and clinical outcomes in high-grade serous ovarian cancer (HGSOC) patients. The MALDI-TOF mass spectrometry assays revealed a strong association between hypermethylation of the MGRN1 upstream region and platinum resistance in HGSOC patients. Spearman’s correlation analysis revealed a significantly negative connection between the methylation level of MGRN1 and its expression in HGSOC. In vitro analysis demonstrated that knockdown of MGRN1 reduced the sensitivity of cells to cisplatin and that expression of EGR1 was significantly decreased in SKOV3 cells with low levels of MGRN1 expression. Similarly, EGR1 mRNA expression was lower in platinum-resistant HGSOC patients and was positively correlated with MGRN1 mRNA expression. Kaplan-Meier analyses showed that high methylation of the MGRN1 promoter region and low expression of MGRN1 were associated with worse survival of HGSOC patients. In multivariable models, low MGRN1 expression was an independent factor predicting poor outcome. Furthermore, low expression of EGR1 was also been confirmed to be significantly related to the poor prognosis of HGSOC patients by Kaplan-Meier. The hypermethylation of the MGRN1 promoter region and low expression of MGRN1 were associated with platinum resistance and poor outcomes in HGSOC patients, probably by altering EGR1 expression.